Integrating transcriptomic and metabolomic analyses to characterize the potential function of SLC1A5 in thyroid cancer - Fengling Shan; Lan Wang; Xinyu Lu; Meihong Zhou; Zi Wang; Jingjing Lou; Xingdang Liu (BMC Cancer)
Abstract Background Alanine Serine Cysteine transporter 2 (ASCT2/SLC1A5) is a key glutamine transporter in cancer cells and has been shown in a variety of cancers to promote tumor growth by reprogramming glutamine metabolism and altering the tumor microenvironment. However, the role in thyroid cancer remains unknown. Methods To investigate the expression and prognostic value of SLC1A5 in thyroid cancer using publically available databases, and to define the relationship with clinical characteristics. SLC1A5 expression in TPC-1 and B-CPAP was knocked down using SLC1A5 siRNA to investigate its effects on cell growth and apoptosis. Transcriptome sequencing and metabolite analysis were carried out in the SLC1A5 siRNA group to identify major transcriptomic or metabolite changes that could lead to apoptosis. In addition, we explored for the connection of SLC1A5 with the tumor microenvironment using algorithms like ESTIMATE and CIBERSORT. Results High SLC1A5 expression in THCA is related with a poor prognosis and advanced clinical stage. In vitro findings showed that SLC1A5 knockdown reduced THCA cell activity and accelerated apoptosis, and the results were consistent with the effect of SLC1A5 inhibitor GPNA. While RNA sequencing analysis revealed that NF-κb signaling was enhanced and oxidative phosphorylation levels were lowered. Metabolomics findings indicated that Glutathione and purine metabolism were dramatically affected in the SLC1A5 siRNA group. Furthermore, immune microenvironment study revealed that SLC1A5 had a positive correlation with the amount of CD4 + T memory-activated cells and T cell follicular helper cells. Conclusion SLC1A5 may be a possible target in THCA. Our findings indicate that DEGs and differential metabolites are mostly linked to numerous signaling pathways and immunological modulation, which may play an important role in SLC1A5 regulation of THCA development.